2017
DOI: 10.5194/gmd-10-709-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal approach to moving window block kriging of satellite data v1.0

Abstract: Abstract. Numerous existing satellites observe physical or environmental properties of the Earth system. Many of these satellites provide global-scale observations, but these observations are often sparse and noisy. By contrast, contiguous, global maps are often most useful to the scientific community (i.e., Level 3 products). We develop a spatio-temporal moving window block kriging method to create contiguous maps from sparse and/or noisy satellite observations. This approach exhibits several advantages over … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Neural networks (NNs), together with many other machine learning algorithms, have been used with remote sensing datasets in the Earth sciences, especially for carbon and water fluxes estimation (Alemohammad et al, 2017;Jung et al, 2011;Tramontana et al, 2016), land cover mapping (Kussul et al, 2017;Zhu et al, 2017), soil moisture retrievals and downscaling (Alemohammad et al, 2018;Kolassa et al, 2018) or to bypass parameterization . These studies mostly attempted to link the satellite signals with limited in situ observation or model simulations for model training, while taking advantage of the large amount of data in remote sensing observations; they applied the trained algorithm to generate a regional or global dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Neural networks (NNs), together with many other machine learning algorithms, have been used with remote sensing datasets in the Earth sciences, especially for carbon and water fluxes estimation (Alemohammad et al, 2017;Jung et al, 2011;Tramontana et al, 2016), land cover mapping (Kussul et al, 2017;Zhu et al, 2017), soil moisture retrievals and downscaling (Alemohammad et al, 2018;Kolassa et al, 2018) or to bypass parameterization . These studies mostly attempted to link the satellite signals with limited in situ observation or model simulations for model training, while taking advantage of the large amount of data in remote sensing observations; they applied the trained algorithm to generate a regional or global dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited applications to groundwater, spatiotemporal kriging is common to a number of other environmental studies. These studies include the analysis and mapping of precipitation (Martínez et al, ); MODIS temperature and precipitation (Hengl et al, ; Hu et al, ); soil moisture, temperature, and electrical conductivity (Gasch et al, ; Wang et al, ); satellite‐observed CO 2 (Tadic et al, ; Tadić et al, ; Zeng et al, ); ozone data (Xu & Shu, ); NO 2 pollutants (Beauchamp et al, ; De Iaco & Posa, ); standardized precipitation index (Bayat et al, ); gamma dose rates (Heuvelink & Griffith, ); solar irradiance forecasting (Aryaputera et al, ); and soil heavy metal distribution (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial-only geostatistical methods do not take into account the temporal correlation structure of CO 2 data [19], which may provide extra information. In order to make full use of spatio-tempal correlation of atmospheric CO 2 , a new spatio-temporal kriging method was developed for the global mapping of XCO 2 [19,36]. Because these methods were previously used for observations from a single satellite, measurement error could be assumed to be uniform and not interfere with the kriging approach.…”
mentioning
confidence: 99%